. FIRST MOLECULAR DETECTION OF LEISHMANIA INFANTUM IN SERGENTOMYIA MINUTA (DIPTERA, PSYCHODIDAE) IN ALENTEJO, SOUTHERN PORTUGAL - Pereira, S. (2018)
One Sergentomyia minuta female was positive for L. infantum infection and another for human blood as a meal source.